A Novel Soft Switching DC–DC Boost Converter with Higher Efficiency. Issue 4 (4th July 2021) - Pakdel, M.; Taheri, A.; Jalilzadeh, S.
Abstract : The current study proposes a novel zero voltage and zero current (ZVZCS) soft switching pulse-width modulated (PWM) DC–DC boost converter. In the proposed converter, the main switch and the auxiliary switch are turned on by zero voltage switching (ZVS) and off by zero current switching (ZCS). There is no additional voltage or current stress on the power switches. The proposed topology has a simple structure. The strategy used to control the power devices is simple and implementation is straightforward. The proposed topology for the soft switching PWM DC–DC boost converter was analysed using simulation, and an experimental prototype was built to verify the theoretical analysis and simulation results.